Age-Related Changes in Murine Corneal Nerves. (2nd August 2016) - Reichard, Maria; Weiss, Heike; Poletti, Enea; Ruggeri, Alfredo; Guthoff, Rudolf F.; Stachs, Oliver; Baltrusch, Simone
ABSTRACT: Purpose : The aim of this study is to determine age-related morphological changes in the corneal subbasal nerve plexus (SNP) in two inbred mouse strains. Materials and methods : The corneal SNP was investigated by in vivo confocal laser scanning microscopy (CLSM) in 0.5-, 1-, 1.5-, and 2-year-old C57BL/6J mice and in 0.5- and 1-year-old BALB/c mice ( n = 4 per age category and strain; 10 images per mouse). Fixed corneal samples from C57BL/6J mice were also analyzed after PGP9.5 staining. Nerve fiber density (NFD) was determined using the semi-automated NeuronJ program. In addition, a new custom-designed, fully automated computerized technique based on oriented multiscale matched filtering was tested to objectify and accelerate image analysis. Results : C57BL/6J mice showed low NFD (11.7 ± 0.5 mm/mm 2 ). Aging from 0.5 to 1, 1.5, and 2 years resulted in significant reductions in subbasal NFD by 34%, 49%, and 66%, respectively. The decline in nerve fibers revealed by in vivo CLSM together with NeuronJ quantification was confirmed by ex vivo immunohistochemical analyses. Subbasal NFD in BALB/c mice (30.0 ± 1.4 mm/mm 2 ) was 3-fold higher than in C57BL/6J mice. Aging from 0.5 to 1 year resulted in a significant 17% reduction in NFD. With the automated approach, NFD of 22.6 ± 2.9 mm/mm 2 and a 45% reduction during aging was determined from the same images. Conclusions : An age-related reduction in subbasal corneal nerve fibers was observed. The differing extent of reduction in the two mouse strains may be accounted for by genetic factors. Automated NFD quantification of corneal nerve fibers in mice appears to be a useful, reliable, objective, and time-saving tool.